Gastroprotective Effect of Acacia aroma Gill. ex Hook. and Arn: Leaves Extracts in Gastric Ulcer Models in Rats - Taboada, Félix Facundo (2019)
Background: Peptic ulcer is a disease caused by imbalance between protective and aggressive factors in the gastric mucosa. Acacia aroma Gill.ex Hook. and Arn. (tusca) is widely used in Argentinian?s folk medicine forgastrointestinal disorders. The present study was designed to evaluatethe protective effect of two A. aroma leaf extracts, 5% infusion and 10%hydroalcoholic extract in experimental models of acute gastric ulcerationin rats. Methods: The gastroprotective action of the extracts was evaluated in absolute ethanol-induced gastric lesion models in adult Westarrats through macroscopic, histological and biochemical analyses of thestomach and gastric wall. We also determined the effects on the gastricjuice parameters with a pylorus ligature model in rats. Evaluation of theacute toxicity of each extract was performed in adult normal Wistar rats.All results were statistically analyzed. Results: The lowest effective dosewas 150 mg/Kg for each extract. Both of them showed a high protectionof the mucosa against absolute ethanol. Pre-treatments with the extractsproduced a significant increase in adherent mucus. These extracts showeda free radical scavenging capacity and they caused a significant reductionof the malondialdehyde, reduced glutathione levels, catalase and myeloperoxidase activities. The animals presented no signs of acute toxicityindicating a high safety margin for both extracts. Conclusion: This studyshows for the first time the gastroprotective efficacy of 5% infusion and10% hydroalcoholic extract of A. aroma leaves, highlighting their benefitsas a prophylactic approach to maintain the integrity of the gastric mucosa.